Răspuns :
63+{9·[18+(2x-4):2]}·3=576
{9·[18+(2x-4):2]}·3=576-63
{9·[18+(2x-4):2]}·3=513
9·[18+(2x-4):2]=513:3
9·[18+(2x-4):2]=171
18+(2x-4):2=171:9
18+(2x-4):2=19
(2x-4):2=19-18
(2x-4):2=1
2x-4=1·2
2x-4=2
2x=2+4
2x=6
x=6:2
x=3
{9·[18+(2x-4):2]}·3=576-63
{9·[18+(2x-4):2]}·3=513
9·[18+(2x-4):2]=513:3
9·[18+(2x-4):2]=171
18+(2x-4):2=171:9
18+(2x-4):2=19
(2x-4):2=19-18
(2x-4):2=1
2x-4=1·2
2x-4=2
2x=2+4
2x=6
x=6:2
x=3
{9*[18+(2x-4):2]}*3=576-63
{9*[18+(2x-4):2]}=513:3
9*[18+(2x-4):2]=171
18+(2x-4):2=171:9
(2x-4):2=19-18
2x-4=2
2x=6
x=3
{9*[18+(2x-4):2]}=513:3
9*[18+(2x-4):2]=171
18+(2x-4):2=171:9
(2x-4):2=19-18
2x-4=2
2x=6
x=3